Predictors and prognosis of RV function in pulmonary hypertension due to heart failure with reduced ejection fraction. (14th October 2021) - Schmeisser, A; Rauwolf, T.H; Groscheck, T; Fischbach, K; Luani, B; Kropf, S; Tanev, I; Hansen, M; Meissler, S; Schaefer, K; Steendijk, P; Braun-Dullaeus, R
Abstract: Background and aims: Failure of right ventricular (RV) function worsens outcome in pulmonary hypertension (PH). The adaptation of RV contractility to afterload, the RV-pulmonary artery (PA) coupling, is defined by the ratio of RV end-systolic to PA elastances (Ees/Ea). Using pressure volume loop (PV-L) technique we aimed to identify an Ees/Ea cutoff predictive for overall survival and to assess hemodynamic and morphologic conditions for adapted RV function in secondary PH due to Heart Failure with Reduced Ejection Fraction (HFREF). Methods: This post hoc analysis is based on 112 patients of the prospective Magdeburger Resynchronization Responder Trial. All patients underwent right and left heart echocardiography, and a baseline PV-L and RV catheter measurement. A subgroup of patients (n=50) without a pre-implanted cardiac device underwent MRI at baseline. Results: The analysis revealed that 0.68 is an optimal Ees/Ea cutoff (area under the curve: 0.697, p<0.001) predictive for overall survival (median follow up = 4.7 years, Ees/Ea ≥0.68 vs. <0.68, log-rank 8.9, p=0.003. In patients with PH (n=76, 68%) Multivariate Cox-regression demonstrated the independent prognostic value of RV-Ees/Ea in PH patients (HR 0.2, p<0.038). Patients without PH (n=36, 32%) and those with PH but RV-Ees/Ea ≥0.68 showed comparable RV-Ees/Ea ratios (0.88 vs. 0.9, p=0.39), RV size/function, and survival. In contrast, secondary PH with RV-PA coupling ratio Ees/Ea <0.68 corresponded extremely close to cut-off values that define RV dilatation/remodeling (RVEDV >160ml, RV-mass/volume-ratio <0.37 g/ml) and dysfunction (RVEF <38%, TAPSE <16mm, FAC <42%, and stroke-volume/end-systolic volume ratio <0.59) and is associated with a dramatically increased short and medium-term all-cause mortality. Independent predictors of prognostically unfavorable RV-PA coupling (Ees/Ea <0.68) in secondary PH were a preexistent dilated RV (end-diastolic volume >171ml, odds ratio, OR 0.96, p=0.021), high pulsatile load (PA compliance <2.3 ml/mmHg, OR 8.6, p=0.003), and advanced systolic left heart failure (left ventricular (LV) ejection fraction <30%, OR 1.23, p=0.028). Conclusions: The RV-PA coupling ratio Ees/Ea predicts overall survival in PH due to HFREF and is mainly affected by pulsatile load, RV remodeling and LV dysfunction. Prognostically favorable coupling (RV-Ees/Ea ≥0.68) in PH was associated with preserved RV size/function and mid-term survival, comparable to HFREF without PH. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific